Preventing Child Sexual Abuse: Body Safety Training for Young Children in Turkey - Tunc, Gulseren Citak; Gorak, Gulay; ÖZYAZICIOĞLU, NURCAN; AK, BEDRİYE; IŞIL, ÖZLEM; IŞIL, ÖZLEM; Vural, Pinar (My University, 2018)
The Body Safety Training Program is an education program aimed at ensuring children are informed about their body and acquire self-protection skills. In this study, a total of 83 preschoolers were divided into experimental and control groups; based on a power analysis, 40 children comprised the experimental group, while 43 children comprised the control group. The Body Safety Training Programme was translated into Turkish and content validity was determined regarding the language and cultural appropriateness. The What If Situations Test (WIST) was administered to both groups before and after the training. Mann-Whitney U Test, Kruskal-Wallis Variance Analysis, and the Wilcoxon Signed Ranks Test were used to compare between the groups and the Spearman correlation analysis was used to determine the strength of the relationship between the dependent and independent variable. The differences between the pretest and posttest scores for the subscales (appropriate recognition, inappropriate recognition, say, do, tell, and reporting skills), and the personal safety questionnaire (PSQ) score means for the children in the experimental group were found to be statistically significant (p<.001). The posttest-pretest difference score means of the experimental group children for WIST saying, doing, telling and reporting, total skills, and PSQ were found to be statistically significant as compared to that of the control group (p<.05). The Body Safety Training programme is effective in increasing the child sexual abuse prevention and self-protection skills in Turkish young children.